Perkembangan Instrumen Sukuk Negara Dalam Pembangunan Infrastruktur Di Indonesia - Hidayatul Amaliyah; Faries Adjie Prayogie; Khoirotul Islamiyah; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
Infrastructure development plays an important role for the prosperity of society. SBSN is issued with the aim of financing the State Budget including infrastructure development. This research was conducted to determine the linkages of sukuk in infrastructure development in Indonesia. This study uses a qualitative descriptive method with a literature study approach, namely reviewing, analyzing, looking for problem theories that are related to the research theme. The data used is data sourced from literature or references. The analysis technique in this study uses a technique that combines concepts and theories regarding the development of sukuk, infrastructure development, as well as the State Revenue and Expenditure Budget (APBN), and State Sharia Securities (SBSN). The research finding is that state sukuk have an important influence on funding infrastructure development with the PBS (Project Based Sukuk) and Retail State sukuk series.